Transformation of the Education of Moderate Muslim Society: A Thought Study of Nahdlatul Ulama - Hasbiyallah; Sulhan, Moh.; Khoiruddin, Heri (Jurnal Pendidikan Islam, 2017)
Indonesia is a country which not only consists of various tribes, ethnicity, and religions but also established on the multi-cultural element. The plurality, on one hand, is a social strength and a wonderful aspect of diversity if each of those aspects makes synergy and works together to build the nation. On the other hand, the plurality, if it is not managed and nurtured properly, will trigger and ignite conflict and violence that could destabilize the joints of the state and nation. In this case, Nahdlatul Ulama (NU) has a strategic role in building a moderate Indonesian Muslim community because NU offers a model of integration, namely the integration of Islam into nationalism. It is the integration of Islamic visions of life into the main objectives of the establishment of nation-states. The idea departs from the principle of al-Ghayah wa al-Wasail (the objectives and the methods) that NU puts the state as an instrument for achieving the goal of Islam. Thus, since the aim of Islam is Rahmatan lil ‘Alamin (welfare of the universe), the state that leads to the goal can be accepted, though not in the form of the Islamic state. NU’s concept in the transformation of education among moderate Muslim society accentuates on the principle of tasamuh (tolerance), tawazun (balance), and i’tidal (just). These three concepts will form the Indonesian Islamic community that is tolerant, peaceful, and Rahmatan lil ‘Alamin for the life of the nation.